Comparative evaluation of the effect of blue M active oxygen gel and Coe-Pack dressing on postoperative surgical depigmentation healing: A clinical study - Tusharika Sharma; Neeraj Deshpande; Monali Shah; Rashmi Jha (SRM Journal of Research in Dental Sciences)
Background: The substantial saturation of the gingiva poses a significant esthetic issue for multiple individuals. Melanin saturation arises from melanin located within the gingival epithelium. Even though surgical depigmentation using a scalpel remains the favored system for managing gingiva pigmentation, it affects open wounds requiring specific dressing and management. Aim: The purpose of the study was to evaluate and compare the efficacy of Coe-Pack dressing and BlueM active oxygen gel in reducing pain after surgical depigmentation and evaluating gingival healing. Materials and Methods: Thirty-four nonsmoking individuals aged 20–38 years with physiologic gingival pigmentation index III and IV according to the Dummett–Gupta Oral Pigmentation index were enrolled in this split-mouth randomized clinical trial. These individuals were selected for an esthetic treatment for gingival hyperpigmentation of the gingiva. After depigmentation with a scalpel, the maxilla and mandible were separated to admit either BlueM gel or Coe-Pack as a dressing. A 1-week, 2 weeks, 3 weeks, and 4 weeks long follow-up period was observed, and indices, including the Dummet–Gupta Oral Pigmentation Index and re-epithelization index using toluidine blue dye, were evaluated and the Visual Analog Scale Pain index was also evaluated at 2 h, 24 h, 2 days, 3 days, 4 days, 5 days, 6 days, and 7 days follow-up period. Results: In total, 34 surgical sites were covered in this investigation. The pain indicator showed statistically significant variations from 1 day to 5 days later. After 3 weeks, the reepithelization index showed an advanced meaningful difference in the BlueM gel group. Conclusion: BlueM gel’s pain reduction, wound healing acceleration, and postoperative reepithelization make it a viable choice for the Coe-Pack dressing following gingival depigmentation.